Whole Genome Sequencing Identifies Key Genes in Spinal Schwannoma - Gao, Xin; Zhang, Li; Jia, Qi; Tang, Liang; Guo, Wen; Wang, Tao; Wu, Zheyu; Zhou, Wang; Li, Zhenxi; Xiao, Jianru (Frontiers in Genetics, 2020)
Spinal schwannoma is the most common primary spinal tumor but its genomic landscape and underlying mechanism driving its initiation remain elusive. The aim of the present study was to gain further insights into the molecular mechanisms of this kind of tumor through whole genome sequencing of nine spinal schwannomas and paired blood samples. The results showed that ATM, CHD4, FAT1, KMT2D, MED12, NF2, and SUFU were the most frequently mutated cancer-related genes. In addition, the somatic copy number alterations (CNA) was potentially associated with spinal schwannoma, among which NF2 was found to be frequently deleted in schwannoma samples. Only a few genes were located within the amplified regions. In contrast, the deleted regions in 15q15.1 and 7q36.1 contained most of these genes. With respect to tumorigenesis, NF2 had the highest variant allele frequency (VAF) than other genes, and homozygous deletion was observed in NF1, NF2, and CDKN2C. Pathway-level analysis suggested that Hippo signaling pathway may be a critical pathway controlling the initiation of spinal schwannoma. Collectively, this systematic analysis of DNA sequencing data revealed that some key genes including NF1, NF2, and CDKN2C and Hippo signaling pathway were associated with spinal schwannoma, which may help improve our understanding about the genomic landscape of spinal schwannoma.